Trabalho remoto em contexto pandêmico: da organização à desorganização do trabalho de docentes que atuam no ensino superior - Oliveira, Juliane de (2023)
With the advent of the covid-19 pandemic, changes occurred in the teacher’s work. With this premise, the present research aims to: analyze the reorganization and disorganization of the work of teachers who work in Higher Education in the Business Administration course in a Brazilian public institution based on teleworking imposed by the covid-19 pandemic. Initially, a literature review is carried out regarding compulsory teleworking, discussed in light of the concepts of control over the work process, free time and available time, control of subjectivity and organization of workers; presents a brief discussion about the organization of university professors’ work from the 20th century onwards and the precariousness of teaching work during Emergency Remote Teaching. Next, we seek to expose the research method that comes close to the proposal of Concrete Critical Ontology and Epistemology, based on a qualitative approach, of an analytical-descriptive nature, of the ex-post-facto type, which encompasses the period between 2020 and 2022, in which the initial date involves the declaration of the covid-19 Pandemic by the World Health Organization (WHO) and the final date corresponds to the majority return of in-person activities. Nine professors who work in Higher Education on the Business Administration course participated in the research. Data were collected through semi-structured interviews and institutional normative documents. Data analysis is based on content analysis. Next, the research results are presented, which highlight the changes that occurred in teaching work during the pandemic context. Among the elements of reorganization are: technological adaptations in carrying out remote activities; changes in teachers’ professional and personal routines; the extension of the working day and intensification of work; the lack of a support network; and, the lack of support and/or resources from the educational institution studied. The data revealed contradictions in the teachers’ perception, in which aspects considered as advantageous at certain times also became challenges at others and also that teleworking, in a pandemic context, disorganizes teaching work by drastically modifying the conventional forms of the teaching-learning process, casting doubt on the effectiveness of teaching methods, educational approaches and pedagogical strategies used to share information with students, as well as hindering interaction between teachers and students. It is considered important to recognize all these challenges that are part of the teaching profession and think about ways to improve the working conditions of these professionals, not only during teleworking, but also in other situations. It is necessary, at the same time, to fight for more sensitive policies and appropriate support to ensure that teachers are treated with due attention, without being forced to compromise their health for the sake of work. Reinforcing the concept that ensuring the safety and well-being of workers is a collective responsibility, the actions taken by unions and teaching associations, in collaboration with groups and communities, play a vital role and must be encouraged and strengthened.